Answer: ![x=-1](https://tex.z-dn.net/?f=x%3D-1)
<u>Add 8x to both sides</u>
<u></u>
<u></u>
<u></u>
<u>Subtract 1 from both sides</u>
<u></u>
<u></u>
<u></u>
<u>Divide both sides by 14</u>
<u></u>
<u></u>
Answer:
p =
and q = ![\frac{6}{13}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B13%7D)
Step-by-step explanation:
Given equations:
2p - 3q = 4 -----------(i)
3p + 2q = 9 ------------(ii)
Let's solve this equation simultaneously using the <em>elimination method</em>
(a) Multiply equation (i) by 3 and equation (ii) by 2 as follows;
[2p - 3q = 4] x 3
[3p + 2q = 9] x 2
6p - 9q = 12 -------------(iii)
6p + 4q = 18 -------------(iv)
(b) Next, subtract equation (iv) from equation (iii) as follows;
[6p - 9q = 12]
<u> - [6p + 4q = 18] </u>
<u> -13q = -6 </u> -----------------(v)
<u />
<u>(c)</u> Next, make q subject of the formula in equation (v)
q = ![\frac{6}{13}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B13%7D)
(d) Now substitute the value of q =
into equation (i) as follows;
2p - 3(
) = 4
(e) Now, solve for p in d above
<em>Multiply through by 13;</em>
26p - 18 = 52
<em>Collect like terms</em>
26p = 52 + 18
26p = 70
<em>Divide both sides by 2</em>
13p = 35
p = ![\frac{35}{13}](https://tex.z-dn.net/?f=%5Cfrac%7B35%7D%7B13%7D)
Therefore, p =
and q = ![\frac{6}{13}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B13%7D)
Answer: 40 + 0.21t
Step-by-step explanation:
If t is the number of texts last month and the initial fee for each month is $40 then you will have the expression 40+0.21t
Answer:
first one: <u>3</u>
second one: <u>b</u>
third one: <u>3.2</u>
Step-by-step explanation:
first one:
21 x ________ ÷ 3 = 21
rewrite equation:
21 ÷ 3 x ___ = 21
7 x ___ = 21
(21 / 7 = 3)
7 x 3 = 21
second one:
b x h ÷ h = ___
B
third one:
876 x 3.2 ÷ ______ = 876
2803.2 ÷ ___ = 876
(2803.2 / 876 = 3.2)
2803.2 x 3.2 = 876